From Irony to Solidarity: Affective Practice and Social Media Activism - Nikunen, Kaarina (Studies of Transition States and Societies, 2017)
This article discusses affective practice in context of social media activism. Drawing on work by Margaret Wetherell the article explores particular sensibility of political discourse and action, enhanced by the social media environment. The empirical cases involve the social media activism of anti-immigrant movement as well as solidarity activists in the context of the so called refugee crisis in Europe. It is argued that practices and sensibilities of activism enhanced and shaped by the technologies and economics of social media. While the anti-immigrant movement makes use of politics of irony on various levels from discourse to acts of trolling, solidarity movements tend to focus on compassionate, yet increasingly practical and shielded forms of practices as well as commercialized. Finally it introduces solidarity of dissonance as an opportunity for reflexive collective action and as a space to imagine alternatives.